DOG1 as a novel antibody-drug conjugate target for the treatment of multiple gastrointestinal tumors and liver metastasis - Wu, Yangping; Li, Wenting; Chen, Xiangzheng; Wang, Haichuan; Su, Siyuan; Xu, Ying; Deng, Xiangbing; Yang, Tinghan; Wei, Mingtian; Li, Li; Liu, Yixin; Yang, Jinliang; et al. (Frontiers in Immunology, 2023)
Discovered On Gastrointestinal stromal tumors protein 1 (DOG1), a major calcium-activated chloride channel, has been used as a common diagnostic marker for gastrointestinal stromal tumors. However, the therapeutic application of DOG1 was not well defined. Here, we aim to investigate its potential as a therapeutic target for an antibody-drug conjugate (ADC) in various cancers of the alimentary tract and metastasis. The DOG1 expression profile was determined among TCGA samples and tissue microarrays. High levels of DOG1 expression were ubiquitously observed in multiple cancer samples from the alimentary tract determined by TCGA samples and tissue microarrays. Circulating tumor cells isolated from metastatic colon cancer patients were also positive for DOG1 expression. The mechanisms of anti-DOG1 antibody were investigated by dual-luciferase reporter assay. The anti-DOG1 antibody could inhibit proliferation and metastasis via p53 signaling in limited cancer cell lines. The anti-DOG1 antibody was conjugated with a microtubule inhibitor DM4, to construct a new anti-DOG1-DM4-ADC to strengthen its activity. The anti-DOG1-DM4-ADC showed cytotoxicity at the nanomolar level in vitro. In the murine xenograft tumor models, treatment of anti-DOG1-DM4-ADC achieved a significant tumor growth inhibition rate. Our study indicates that anti-DOG1-DM4-ADC may be promising therapeutic molecules for DOG1-positive alimentary tract tumors and may be effective in inhibiting recurrence after curative resection of liver metastases of colorectal origin.